Barriers to reporting hate crime: A Welsh perspective. (September 2020) - Cuerden, Gareth J; Blakemore, Brian
This study gathered 197 participants, interviewed within 48 hours of being victims of Hate Crime. This immediate follow-up should ensure accurate responses. The responses of the victims were compared to that of 113 Welsh front-line staff who respond to and support such victims. The barriers to reporting are found to be broadly similar with the findings of other UK studies. A considerable difference in understanding of the barriers to reporting hate crime was found between the victims and support services. The main reason given for non-reporting was common: the poor service, attitude and treatment from the police.